Bioconversion of Paddy Straw into Vermicompost through Fungal-Earthworm Interactions - Viji Jayabalan; Periyasamy, Neelanarayanan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Aim: The primary aim of this research work is to utilize fungal consortium (Aspergillus oryzae, Aspergillus fumigatus and Rhizopus oryzae) for the partial degradation of paddy straw and thereafter to study the vermicomposting ability with Eudrilus eugeniae, Perionyx excavatus and Lampito mauritii under monoculture (E I, E II and E III, respectively) and polyculture (E IV) conditions. The pre-digested paddy straw was used in combination with cow dung (1:1 ratio). Materials and Methods: This study was conducted for over a period of 50 days. Four experimental treatments i). E I (experimental trays inoculated with E. eugeniae) ii). E II (experimental trays inoculated with P. excavatus) iii) E III (experimental trays inoculated with L. mauritii) and iv) E IV (experimental trays inoculated with E. eugeniae, P. excavatus and L. mauritii) were used for the present study. At the end of the experiments, the chemical nutrients, biological composition were quantified. Results: The vermicompost obtained from E IV and E I experimental trays were comparatively rich in macro and micro nutrients, microbial populations than the others. Conclusion: It can be concluded that paddy straw can be pre-digested with a selected fungal consortium and subsequently converted into vermicompost using earthworms, either in monoculture (E. eugeniae) or polyculture (E. eugeniae, P. excavatus, and L. mauritii) systems.